Sexy sports: a reception study of the National Broadcasting Corporation (NBC) Olympics website coverage of women's beach volleyball at the 2008 Beijing Olympics - Tajdin, Wafa Mohamed (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2010)
Sexy Sports: A reception study of the National Broadcasting Corporation (NBC) Olympics website coverage of women's beach volleyball at the 2008 Beijing Olympics involves an examination of the sporting media and its reportage of the female athlete. The thesis will focus on the reception of the NBC Olympics website coverage of women's beach volleyball at the 2008 Beijing Olympics by viewing groups constituted by the researcher. The reason for this is that it would be difficult to find naturally constituted audiences for this website, but its reception is never-the-less of research interest. My hypothesis is that the nature of the images and text on the website is overdetermined by the construction of women on other popular texts such as men's magazines etc. In focusing on the meanings obtained from the content of the website (texts and images), the study will investigate how these meanings are naturalised in specific moments of production as well as through their intertextual relationships with similar texts involved in the glamorisation of female athletes. Specifically the study explores the meanings obtained from the content of the website (texts and images) and how in turn these meanings are naturalised by the consumers of the website. The study will utilise a qualitative research design to unpack the content of the website through the use of qualitative content analysis, focus group interviews and individual in-depth interviews. The research will be informed via a theoretical framework that draws from feminist theory, sport feminism, the concept of intertextuality between media texts, ideology and Stuart Hall's model of preferred reading. Increasingly mainstream media uses the image of a woman's body to sell almost anything from men's razors to margarine and in so far as the reporting of women's sports is concerned this holds true. Through the research I intend to account for the connotative power of other texts i.e. the men's magazines and pornography, and how this is likely to be carried through into shaping the meanings that are read off the website. Arguably the production of the NBC texts and images are overdetermined by the existence of similar texts already in transmission in the circuit of culture.
Keywords: Olympics National Broadcasting Company; Sports journalism; Mass media and sports; Volleyball for women; Beach volleyball; Feminism and mass media; Cyberfeminism; Sexism in mass media; Women athletes; Sports for women; Sex role in mass media; Women in mass media